2021
DOI: 10.1055/s-0041-1723965
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Pediatric Bone Tumors and Tumor-like Lesions

Abstract: Bone lesions are commonly seen when reporting pediatric skeletal imaging. Distinguishing aggressive from nonaggressive lesions is essential in making the diagnosis. Not all aggressive lesions are neoplastic; indeed, osteomyelitis frequently presents with aggressive appearances and is far more commonly seen in the pediatric population than neoplastic lesions. In this article, we discuss an approach for the diagnosis of pediatric bone tumors and tumor-like conditions. The most common pediatric benign and maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…It often has a soft tissue mass, and the main form of the lesion is a circular arc shape, with internal flute calcification, spot shape or annular, and there is a difference in calcification of different soft bone tumors [16]. e study analyzed the image characteristics of primary isolated bone tumor and tumor morphology of the iliac bone, and the results showed that the round highdensity shadow, soft tissue swelling, soft tissue mass, right bowel, and bladder were significantly compressed [17]. e results confirmed that there is a lesionic imaging characteristics to identify a variable and malignant tumor, often through the osteospondel cartilage cap, osteogenic protrusion, soft tissue mass, tumor calcification, plaque shape, jet tumor bone, and clinical diagnosis, which can be used for diagnosis and formulation of treatment options [18].…”
Section: Discussionmentioning
confidence: 99%
“…It often has a soft tissue mass, and the main form of the lesion is a circular arc shape, with internal flute calcification, spot shape or annular, and there is a difference in calcification of different soft bone tumors [16]. e study analyzed the image characteristics of primary isolated bone tumor and tumor morphology of the iliac bone, and the results showed that the round highdensity shadow, soft tissue swelling, soft tissue mass, right bowel, and bladder were significantly compressed [17]. e results confirmed that there is a lesionic imaging characteristics to identify a variable and malignant tumor, often through the osteospondel cartilage cap, osteogenic protrusion, soft tissue mass, tumor calcification, plaque shape, jet tumor bone, and clinical diagnosis, which can be used for diagnosis and formulation of treatment options [18].…”
Section: Discussionmentioning
confidence: 99%